MR Imaging of Nonmalignant Polyps and Masses of the Nasopharynx and Sphenoid Sinus after Radiotherapy for Nasopharyngeal Carcinoma - King, A.D.; Ahuja, A.T.; Leung, S.-F.; Abrigo, J.; Wong, J.K.T.; Poon, W.S.; Woo, K.S.; Chan, H.S.; Tse, G.M.K. (American Journal of Neuroradiology, 2008)
BACKGROUND AND PURPOSE: The development of a new polyp or mass in the radiation field of a previously treated carcinoma is usually an ominous sign of a recurrent cancer, but rarely may it be caused instead by a nonmalignant process. The purpose of this study was to document the MR appearance of unusual nonmalignant polyps or masses (NMPMs) in the nasopharynx and sphenoid sinus arising after radiation treatment of nasopharyngeal carcinoma.MATERIALS AND METHODS: The MR imaging reports of patients undergoing imaging after radiation therapy for nasopharyngeal carcinoma were reviewed retrospectively to identify patients with unusual polyps and masses in the nasopharynx. The MR images of those patients with no evidence of malignancy on biopsy or follow-up were reviewed.RESULTS: The MR imaging reports of 1282 patients were reviewed, and 11 patients (1%) with NMPMs in the nasopharynx or sphenoid sinus were identified. Two patterns were identified: contrast enhancing nasopharyngeal polyps ranging in size from 1 to 5 cm (n = 5) and sphenoid sinus masses consisting of a nonenhancing mass filling a nonexpanded sinus (n = 4) and a heterogeneous enhancing mass expanding the sinus (n = 2). Osteoradionecrosis produced a large defect in the roof of the nasopharynx causing direct communication with the sphenoid sinus (n = 6). Histology revealed granulation tissue in all of the patients with variable amounts of fibrin and inflammatory cells. A direct infective etiology was not proved in any patient.CONCLUSION: NMPMs in the nasopharynx and sphenoid sinus are rare complications after radiation therapy to the skull base, but the radiologist needs to be aware of their appearance so that they can be considered in the differential diagnosis of suspected tumor recurrence.